Design and Simulation of Filter and Antenna Based on Fractal Distribution of Graphene Layers For Terahertz Application - السموءل صالح,; تغريد حداد ,; رنا حسن, (Latakia University Journal -Engineering Sciences Series, 2023)
Graphene has recently arisen as an important material for THz devices due to its extraordinary THz properties inherited from its particular band structure. It has tunable physical and chemical properties in addition to its tunable electrical conductivity. A fractal structure containing Cantor distribution of graphene layers/ dielectric layers are studied and calculated transmission and reflection coefficient. The effect of fractal factors such as stage of growth, fractal dimension on the transmission and reflection coefficient are studied in order to obtain a terahertz filter. Then, we proposed a design of terahertz antenna based on Cantor distribution of graphene, that provides a multi-dimensional structure. The proposed antenna was designed using CST simulator and analyzed the effect of the variation of resonance patch numbers and dimensions on the antenna proprieties.